Ecopedagogía para la formación bioética ambiental en estudiantes de enfermería - Diaz Vasquez, Maribel A. (2020)
It is urgent to become aware to restore and protect the environment, due to the magnitude of environmental destruction worldwide that human beings have produced by allowing themselves to be carried away by a culture of consumerism and waste, without considering the future consequences for the next generations. . The environment is considered a determinant of health, therefore it is important to incorporate it in the study of nursing professionals, being pertinent to use the principles of eco-pedagogy during their training since it focuses not only on environmental education, but also includes the vision of sustainable development, that is, taking care of the environment and making reasonable use of it to improve people's living conditions. This essay aims to reflect on and analyze the importance of eco-pedagogy for the training in environmental bioethics of future nursing professionals.